Sexual disorders in a 45 –year-old patient after hysterectomy in the home - Maria Ciechacka; Agnieszka Pawełko (Journal of Education, Health and Sport)
Hysterectomy is one of the most commonly performed gynecological surgeries in women over 40 years of age. Although this procedure is an effective treatment for conditions such as uterine fibroids, uterine prolapse, and chronic bleeding, its consequences for sexual health remain significant and are often insufficiently addressed in postoperative care. Research findings indicate that between 30% and 50% of patients after hysterectomy experience sexual dysfunction, including vaginal dryness, decreased libido, dyspareunia, and difficulties achieving sexual satisfaction. The presence of these symptoms affects not only the physical condition of women but also their psychological well-being and intimate relationships, especially during the convalescence period, which most often takes place at home.